2003
DOI: 10.1002/cncr.11495
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prognosis of patients with intracranial nongerminomatous malignant germ cell tumors

Abstract: Ionic liquids with their limitless combination of cations and anions can offer an optimal solvent for a specific purpose. But not all corresponding experimental studies are possible as they will be time consuming and expensive. A judicious screening of the various possible solvents is required to select the proper ionic liquid. Conductor‐like screening model (COSMO) along with its extension to real solvents can be used for these predictions. In this work, modified version COSMO_LL has been used to predict the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
57
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 66 publications
(43 reference statements)
2
57
1
Order By: Relevance
“…1,4,19 Nongerminomatous GCTs are relatively resistant to radiation therapy and chemotherapy and are associated with a poor outcome. 9,21,26 Nongerminomatous GCTs consist of heterogeneous histological types, with a significant difference in the prognosis between pure malignant GCT and other types of NGGCTs. 21,26 Intracranial GCTs were divided into 3 groups based on treatment outcomes to establish treatment regimens for germinomas and NGGCTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,19 Nongerminomatous GCTs are relatively resistant to radiation therapy and chemotherapy and are associated with a poor outcome. 9,21,26 Nongerminomatous GCTs consist of heterogeneous histological types, with a significant difference in the prognosis between pure malignant GCT and other types of NGGCTs. 21,26 Intracranial GCTs were divided into 3 groups based on treatment outcomes to establish treatment regimens for germinomas and NGGCTs.…”
mentioning
confidence: 99%
“…9,21,26 Nongerminomatous GCTs consist of heterogeneous histological types, with a significant difference in the prognosis between pure malignant GCT and other types of NGGCTs. 21,26 Intracranial GCTs were divided into 3 groups based on treatment outcomes to establish treatment regimens for germinomas and NGGCTs. A mature teratoma was classified into the good prognosis group.…”
mentioning
confidence: 99%
“…20 It is recognized that, in older children, chemotherapy with platinum agents is effective for intracranial immature teratomas. 11,15,16 It is also known that neoadjuvant chemotherapy can induce differentiation of malignant germ cell tumors into mature teratomas. 8 The apparent tumor maturation presumably reflects the selective chemo-ablation of their actively proliferating components.…”
Section: Discussionmentioning
confidence: 99%
“…As to the analysis of 111 GCTs performed by Sawamura et al (8), the 5-year survival rate of 9 immature teratomas proved to be 67%. Moreover, Ogawa et al (17) reported 24 cases of intermediate prognosis of NGMGCTs. The 5-year survival rate was 68%.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment for the poor prognosis group of NGMGCT patients was not ideally effective. Ogawa et al (17) analyzed the treatment of 41 NGMGCT patients and found the 5-year survival rate to be 8% in the poor prognosis group. In our study, only 1 out of 4 patients grouped in the poor prognosis group are currently alive.…”
Section: Discussionmentioning
confidence: 99%